Education Challenges of Medical Students in Virtual Sitting: Students’ Perspectives about Quality and Satisfaction of E-learning Service during COVID-19 Pandemic - Moradi Fath, Marjan; Rahimi Khalifeh Kandi, Zahra; Latifi, Marzieh; Goodarzi, Elnaz; Estebsari, Fatemeh (Advances in Nursing & Midwifery, 2024)
Introduction: Because the COVID-19 pandemic necessitated the use of e-learning, this study aims to investigate medical students’ perspectives about quality and Satisfaction of the e-learning services provided by the Learning Management System (LMS) during COVID-19 Pandemic in Iran. Methods: This descriptive cross-sectional research study conducted in 2022 in Iran. The statistical population consisted of 455 medical students. For this purpose, the convenience sampling method was used. Required data were collected using a demographic survey and SERVQUAL questionnaire in two parts importance and performance of learning services. Data were analyzed by using descriptive and non-parametric statistical tests in SPSS version 18 with a 5% confidence level. Results: The results showed a negative gap in all dimensions of e-learning service quality. The highest and lowest mean quality gaps were related to responsiveness (-8.22 ± 1.8) and tangibility (-5.86 ± 0.7), respectively. Among the demographic variables, a significant relationship was observed only between education level and assurance dimension of e-learning service quality importance-performance (P<0.05). Conclusions: Based on the findings of the present study, the LMS system has major challenges for the education of medical students. Therefore, to be used in the medical group, fundamental reforms are needed to improve the quality or to be used together with other appropriate methods and technologies in order to gain more satisfaction.